2015
DOI: 10.3390/nu7031881
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Maternal Diet on Kidney Development; an Opportunity to Improve Cardiovascular and Renal Health for Future Generations

Abstract: The leading causes of mortality and morbidity worldwide are cardiovascular disease (high blood pressure, high cholesterol and renal disease), cancer and diabetes. It is increasingly obvious that the development of these diseases encompasses complex interactions between adult lifestyle and genetic predisposition. Maternal malnutrition can influence the fetal and early life environment and pose a risk factor for the future development of adult diseases, most likely due to impaired organogenesis in the developing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 161 publications
0
37
0
1
Order By: Relevance
“…There is a large body of evidence indicating that birth weight can be a potential predictor of programming effects in animal models [ 38 , 39 ]. Some studies reported a decreased birth weight following maternal low quality protein diets [ 40 , 41 ] whereas a different study showed no effect of 21% wheat gluten [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is a large body of evidence indicating that birth weight can be a potential predictor of programming effects in animal models [ 38 , 39 ]. Some studies reported a decreased birth weight following maternal low quality protein diets [ 40 , 41 ] whereas a different study showed no effect of 21% wheat gluten [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, maternal nutritional status plays a critical role in the fetus health [13]. Indeed, a diet containing sufficient amounts of macro-and micronutrients is essential to fetus organogenesis, whereas adverse nutritional conditions during pregnancy may permanently change the structure and function of specific organs, exposing the offspring also to the risk to develop adult diseases [14]. The difficulty to provide the correct nutrition in pregnant women is further complicated in CKD patients, in whom nutritional therapy is a cornerstone of the clinical management of renal diseases [15].…”
Section: Pregnancy In Women With Renal Disease: Nutritional Issuesmentioning
confidence: 99%
“…In species as diverse as amphibians (Berg et al 2009), reptiles (Schwanz et al 2013), teleosts (Meier et al 2010; Celeghin et al 2011), and mammals (Roseboom et al, 2001; Walker et al, 2012; Ganu et al, 2012; Fleming et al, 2015), alterations in embryonic environment can have long-acting effects on development that extend into post-natal life. Mechanisms responsible for this phenomenon include changes in the epigenome (El-Hajj et al 2014; Desai et al 2015) as well as in patterns of organogenesis and differentiation (Fleming et al, 2015; Wood-Bradley et al, 2015). Developmental programming can be beneficial when the deviation in adult phenotype prepares the individual for life in the anticipated postnatal environment but can be harmful when the actual environment is different than expected (Roseboom et al 2001; Armitage et al 2005; Gluckman et al 2007; Warner 2014).…”
Section: Introductionmentioning
confidence: 99%